A commentary on the Gospel of St Luke - Godet, Frederic Louis, 1812-1900; Shalders, E.W. (Edinburgh, Scotland T and T Clark, 1976)
Contents : v. 1 : Introduction, parts 1-3. Includes bibliographical references.
Originally published 1871
Keywords: Bible. N.T. Luke -- commentaries